2007
DOI: 10.1158/1055-9965.epi-07-0197
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use and Risk of Prostate Cancer in the California Men's Health Study Cohort

Abstract: Statins have known anticarcinogenic effects, however, evidence for long-term statin use as effective chemoprevention for prostate cancer is inconsistent. We examined the association between statin use and risk of prostate cancer among 69,047 eligible participants in the California Men's Health Study, a prospective cohort of Northern and Southern California Kaiser Permanente (KP) members, ages 45 to 69 years, initiated in 2002. Prostate cancer cases were identified by linkage to the KP California Cancer Registr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
117
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(128 citation statements)
references
References 68 publications
8
117
2
1
Order By: Relevance
“…4,[6][7][8] Supportive evidence for the potential role of cholesterol in prostate cancer development has been provided by observations that cholesterol-lowering drugs (3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors, commonly known as statins) might be inversely associated with risk of (advanced) prostate cancer. 4,[18][19][20][21] A meta-analysis by Bonovas et al 22 confirmed that use of statins lowers the risk of advanced prostate cancer (relative risk 0.77, 95% CI 0.64-0.93); however, no effect for total prostate cancer risk was found (relative risk 0.95, 95% CI 0.73-1.23). Others proposed that the cholesterol-lowering effects of statins might not be the only reason why these drugs are associated with reduced risk of advanced prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…4,[6][7][8] Supportive evidence for the potential role of cholesterol in prostate cancer development has been provided by observations that cholesterol-lowering drugs (3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors, commonly known as statins) might be inversely associated with risk of (advanced) prostate cancer. 4,[18][19][20][21] A meta-analysis by Bonovas et al 22 confirmed that use of statins lowers the risk of advanced prostate cancer (relative risk 0.77, 95% CI 0.64-0.93); however, no effect for total prostate cancer risk was found (relative risk 0.95, 95% CI 0.73-1.23). Others proposed that the cholesterol-lowering effects of statins might not be the only reason why these drugs are associated with reduced risk of advanced prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…2), and a case-control study nested in the Finnish population (3), each investigating the association between use of statin drugs and prostate cancer. Along with work in the Health Professionals Follow-up Study reported last year by my colleagues and me (4), four prospectively conducted studies now support an inverse association between statin use and, specifically, advanced prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Participants in the CMHCS live in two regions of California, are multiethnic, and are members of a health maintenance organization. In 2002, 33% had ever been dispensed >100 days of a statin, and 19% of the men were considered to have used statins for 5+ years (2). In the Finnish study, all prostate cancer cases diagnosed in the country during 1995 to 2002 were included, and matched controls were sampled from the Population Register Center, apparently via incidence density sampling.…”
Section: Introductionmentioning
confidence: 99%
“…However, the findings of the Shannon et al and Graaf et al studies (14,15) could not be replicated and a reduction in overall prostate cancer risk was not seen in four large, prospectively conducted trials (16)(17)(18)34). In three of these four studies, an inverse relationship with advanced prostate cancer was noted for either current or prior statin use, however an overall, decreased prostate cancer risk was not seen.…”
Section: Resultsmentioning
confidence: 94%